Arbuscular mycorrhizal fungus alleviates anthracnose disease in tea seedlings - Chen, Weili; Ye, Tao; Sun, Qinyu; Niu, Tingting; Zhang, Jiaxia (Frontiers in Plant Science, 2023)
Tea has been gaining increasing popularity all over the world in recent years, and its yield and quality depend on the growth and development of tea plants [Camellia sinensis (L.) Kuntze] in various environments. Nowadays, biotic stress and extreme weather, such as high temperature, drought, waterlogging, pests, and diseases, bring about much pressure on the production of tea with high quality. Wherein anthracnose, which is the most common and serious disease of tea plants, has earned more and more attention, as its control mainly relies on chemical pesticides. Arbuscular mycorrhizal fungi (AMF), forming symbiosis with most terrestrial plants, participate in plant resistance against the anthracnose disease, which was found by previous studies in a few herbaceous plants. However, there are a few studies about arbuscular mycorrhizal (AM) fungal regulation of the resistance to the anthracnose pathogen in woody plants so far. In this paper, we investigated the effect of AMF on the development of anthracnose caused by Colletotrichum camelliae and tried to decipher the pertinent mechanism through transcriptome analysis. Results showed that inoculating AMF significantly reduced the damage of anthracnose on tea seedlings by reducing the lesion area by 35.29% compared to that of the control. The content of superoxide anion and activities of catalase and peroxidase significantly increased (P < 0.05) in mycorrhizal treatment in response to the pathogen with 1.23, 2.00, and 1.39 times higher, respectively, than those in the control. Pathways of plant hormone signal transduction, mitogen-activated protein kinase (MAPK) signaling, and phenylpropanoid biosynthesis might play roles in this regulation according to the transcriptomic results. Further redundancy analysis (RDA) and partial least squares structural equation modeling (PLS-SEM) analysis found that plant hormones, such as auxin and ethylene, and the antioxidant system (especially peroxidase) were of great importance in the AM fungal alleviation of anthracnose. Our results preliminarily indicated the mechanisms of enhanced resistance in mycorrhizal tea seedlings to the anthracnose pathogen and provided a theoretical foundation for the application of AMF as one of the biological control methods in tea plantations.